Navigating the Digital Chasm: An Analysis of Digital Transformation Failures, Organizational Readiness Assessment Methods, and Their Limitations - Koczerga, Maciej (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Digital transformation has become a critical imperative for organizations across industries, yet the success rate of such initiatives remains alarmingly low, with up to 95% failing to achieve their intended outcomes. This research paper provides a comprehensive analysis of the common causes of digital transformation failures, with a particular focus on the limitations of existing organizational readiness assessment methods. The study examines factors such as lack of clear goals, organizational and cultural barriers, insufficient leadership support, technological and resource constraints, and human capital and skills gaps that contribute to the high failure rate of digital transformation projects. The paper also explores various frameworks and methodologies used to evaluate organizational digital readiness, highlighting their shortcomings, including reliance on self-reported data, lack of standardization, emphasis on quantitative metrics, and the dynamic nature of digital technologies. The findings underscore the need for a more holistic and continuous approach to assessing digital readiness to ensure successful digital transformation initiatives. The study concludes by emphasizing the importance of addressing these limitations to enhance the success rate of digital transformation efforts.